(untitled) (The International Journal for Scientific Research, 2024)
This study aims to explore the impact of supply chain management on the efficiency and costs of transportation companies in the Kingdom of Saudi Arabia. The study is of particular importance in light of the major economic transformations witnessed by the Kingdom within Vision 2030, which seeks to enhance economic diversification and improve the efficiency of various sectors, including the transportation sector. The descriptive analytical approach was used to achieve the objectives of the study. Data were collected through a questionnaire distributed to a random sample of 165 transportation companies in the Kingdom, where the sample included supply chain managers and senior management in various companies. The results showed that there is a positive and noticeable impact of effective supply chain management on improving operational efficiency and reducing costs in transportation companies. It was also shown that adopting modern technologies and developing relationships with suppliers and distributors contribute significantly to enhancing the overall performance of companies. Based on these results, the study recommends the need to invest in developing supply chain management systems and adopting modern technology to enhance efficiency and reduce costs, in addition to enhancing cooperation and communication between companies and suppliers to achieve better performance and increase competitiveness in the local and regional market.